The complement system drives local inflammatory tissue priming by metabolic reprogramming of synovial fibroblasts - Friščić, Jasna; Böttcher, Martin; Reinwald, Christiane; Bruns, Heiko; Wirth, Benjamin; Popp, Sebastian; Walker, Kellie Irene; Ackermann, Jochen A.; Chen, Xi; Turner, Jason; Zhu, Honglin; Seyler, Lisa; et al. (Immunity, 2021)
Arthritis typically involves recurrence and progressive worsening at specific predilection sites, but the checkpoints between remission and persistence remain unknown. Here, we defined the molecular and cellular mechanisms of this inflammation-mediated tissue priming. Re-exposure to inflammatory stimuli caused aggravated arthritis in rodent models. Tissue priming developed locally and independently of adaptive immunity. Repeatedly stimulated primed synovial fibroblasts (SFs) exhibited enhanced metabolic activity inducing functional changes with intensified migration, invasiveness and osteoclastogenesis. Meanwhile, human SF from patients with established arthritis displayed a similar primed phenotype. Transcriptomic and epigenomic analyses as well as genetic and pharmacological targeting demonstrated that inflammatory tissue priming relies on intracellular complement C3- and C3a receptor-activation and downstream mammalian target of rapamycin- and hypoxia-inducible factor 1α-mediated metabolic SF invigoration that prevents activation-induced senescence, enhances NLRP3 inflammasome activity, and in consequence sensitizes tissue for inflammation. Our study suggests possibilities for therapeutic intervention abrogating tissue priming without immunosuppression.
CRIS-Team Scopus Importer:2021-04-19
Keywords: arthritis; cell metabolism; cellular senescence; complement system; inflammasome; inflammation; mechanistic target of rapamycin; synovial fibroblasts; tissue priming; trained immunity